Relief of Phosphate Limitation Stimulates Methane Oxidation - Nijman, Thomas P. A.; Amado, André M.; Bodelier, Paul L. E.; Veraart, Annelies J. (Frontiers in Environmental Science, 2022)
Aquatic ecosystems such as shallow lakes and wetlands are important emitters of the greenhouse gas methane (CH4). Increased phosphorus (P) loading is expected to increase CH4 production in these ecosystems. This increased CH4 production can potentially be mitigated by increased CH4 oxidation, but how P availability affects methane-oxidizing bacterial (MOB) community composition and potential CH4 oxidation remains to be tested. Here, we incubated MOB from sediments of four subtropical lakes of different trophic states for seven days at different phosphate (PO43-) concentrations to determine the effects of P on MOB community composition and potential CH4 oxidation. We measured CH4 consumption daily and compared CH4 oxidation during the exponential growth phase. Furthermore, we determined MOB community composition at the end of the incubations using qPCR of the pmoA gene. To test for differences in N and P uptake, we determined bacterial biomass N and P content. We found that increases in PO43- concentrations until 10 µM significantly increased CH4 oxidation. PO43- also increased bacterial biomass P content, while N content was not affected. MOB community composition was not affected by PO43- but more strongly correlated to lake of origin, likely due to the short duration of the incubations. Our results show that PO43- can not only stimulate CH4 oxidation indirectly through increased CH4 production, but also directly by increasing MOB growth. Importantly, these effects only occur at low PO43- concentrations, indicating that at high nutrient loads the increased CH4 oxidation will likely not mitigate the increased CH4 production.